PENGARUH PEMANFAATAN LIMBAH PERKERASAN JALAN UNTUK LASTON AC-BC DENGAN MENGGUNAKAN BAHAN BONGKARAN CAMPURAN BERASPAL - Lambang Basri Said; Maryam H; Hasim (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2022)
Asphalt mixed demolition material is a road pavement waste that is often found on the side of the road as a result of dredging residue, this is an alternative that can be used to contribute to road maintenance and save on the use of oil asphalt and aggregate materials. The purpose of this study was to determine the effect of adding road pavement waste to the AC-BC asphalt mixture and to obtain the characteristics of the AC-BC recycled asphalt mixture pavement when adding various demolition materials. For the mixture with the addition of 0%, 5%, 10%, 15% and 20% asphalt mixture. Stability values ​​are 1664.14 kg, 1518.87 kg, 1359.14 kg, 1206.33 kg and 1049.40 kg. VIM value is 4.55%; 4.80%; 5.21%; 5.78% and 6.23%. the optimum asphalt content (KAO) value is 5.6%; 5.65%; and 5.75% while the addition of unloading 15% and 20% KAO cannot be determined due to the increase in the VIM value in the mixture, which is greater than the specifications. Mixtures that use a lot of asphalt mixture unloading material show a greater VIM value and reduce the value of marshall stability so that it is necessary to limit the use of demolition material, which is a maximum of 10%.